Students' Motivation in Reading English Text: A Qualitative Study in EFL Context - Dakhi, Saniago; Damanik, Ira Soraya (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2018)
This article addresses an objective description and reasons for the student’s motivation in reading English text. Sixty students of tenth grade at SMA Negeri 55 South Jakarta participated on filling in 50 statements of 11 domains of motivation. An interview, another method to collect data needed and to meet a methodological triangulation, was employed to capture the participants’ perspective. Findings revealed that reading curiosity is the highest domain of the students’ motivation (92.22%), and social reason for reading is the lowest one (55.56%). Some interpretations are included in this paper.